Publications - Vickers, J.
Publikationsliste (mit vielen Volltexten) von Prof. J. Vickers vom Neuro-Motor Psychology Laboratory der Universität Calgary mit dem inhaltlichen Schwerpunkt Auge-Hand-Koordination und Blickverhalten in unterschiedlichen Sportarten: 1. Martell, S. G., & Vickers, J. N. (2004). Gaze characteristics of elite and near-elite athletes in ice hockey defensive tactics. Human Movement Science 22: 689-712. 2. Vickers, J. N., Reeves, M. A., Chambers, K. L., & Martell, S. G. (in press). Decision Training:. Cognitive Strategies For Enhancing Performance. Skill Acquisition in Sport: Research, Theory and Practice. (Ed) Williams, A. M., Hodges, N. J., Scott, M. J., & Court, M. L. J. London: Routledge. 3. Brown, L. & Vickers, J. N. (in press). Temporal judgements, hemispheric equivalence, and inter-hemispheric transfer in adolescents with attention deficit hyperactivity disorder. Experimental Brain Research. 4. Vickers, J.N. (2004). The quiet eye: it's the difference between a good putter and a poor one, here's proof. GolfDigest, January, 96-ff. 5. Patla, A. & Vickers, J. (2003). How far ahead do we look when required to step on specific locations in the travel path during locomotion? Experimental Brain Research, 148: 133-138. 6. Rodrigues, S. T., Vickers, J. N. and Williams, A. M. (2002), Head, eye and arm co-ordination in table tennis: An exploratory study. Journal of Sport Sciences, 20, 3, 171-186. 7. Vickers, J. N., Rodrigues, S. T. and Brown, L. N. (2002). Gaze pursuit and arm control of adolescent males diagnosed with attention deficit hyperactivity disorder (ADHD) as compared to normal controls: Evidence of dissociation in processing short and long-duration visual information. Journal of Sport Sciences. 20, 3, 201-216. 8. Hollands, M.A., Patla, A. E. & Vickers, J. N. (2002). "Look where you are going!" Gaze behaviour associated with maintaining and changing direction. Experimental Brain Research, 143: 221-230. 9. Williams, A. M., Vickers J. N. & Rodrigues, S. T. (2002). The effects of anxiety on visual search, movement kinematics, and performance in table tennis: A test of Eysenck and Calvo's processing efficiency theory, Journal of Sport and Exercise Science. 24, 4, 438-456. 10. Harle, S. & Vickers, J. N. (2001). Training quiet eye (QE) improves accuracy in the basketball free throw. The Sport Psychologist, 15, 289-305. 11. Vickers, J. N., Rodrigues, S. T. & Edworthy, G. (2000). Quiet eye and accuracy in the dart throw. International Journal of Sports Vision, 6, 30-36. 12. Vickers, J. N., Livingston, L., Umeris S. & Holden, D. (1999). Decision Training: The effects of complex instruction, variable practice and reduced delayed feedback on the acquisition and transfer of a complex motor skill. Journal of Sport Sciences. 17, 357-367. 13. Vickers J, Patla AE (1999) Object and travel gaze fixation during successful and unsuccessful stepping stone task. Gait & Posture 9(1): S3. 14. Patla, A. & J. N. Vickers (1997). When and where do we look as we approach and step over an obstacle in the travel path. NeuroReport. Vol 8, No 17, 3661-3665. 15. Vickers, J. N. & Adolphe, R. A. (1997). Gaze behaviour during a ball tracking and aiming skill. International Journal of Sports Vision. 4, 1, 18-27. 16. Adolphe R., Vickers, J. N. & LaPlante, G. (1997). The effects of training visual attention on gaze behaviour and accuracy: A pilot study. International Journal of Sports Vision. 4, 1, 28-33. 17. Vickers, J. N. (1996). Visual control when aiming at a far target. Journal of Experimental Psychology: Human Perception and Performance. 2, 22, 342-354. 18. Vickers, J. N. (1996). Control of visual attention during the basketball free throw. American Journal of Sports Medicine. November. Supplement. 3,1, 93-97. 19. Vickers, J. N. (1994). Psychological research in sports pedagogy: Exploring the reversal effect. Sport Sciences Review Journal. 3 (1), 28-40. 20. Vickers, J. N. (1992). Gaze control in putting. Perception. 21. 117-132. 21. Livingston, L., Sandals, L. & J. N. Vickers. (1992). Monitoring the effect of color on performance in an instructional gaming environment visa the analysis if eye movement behavior. Journal of Research on Computing in Education. 25, 27-45.